Enhanced performance of PbS-sensitized solar cells via controlled successive ionic-layer adsorption and reaction1. Issue 15 (21st April 2015) - Abbas, Muhammad A.; Basit, Muhammad A.; Park, Tae Joo; Bang, Jin Ho
<x xml:space="preserve">Abstract</x> The performance of PbS-sensitized solar cells is significantly improved by controlling successive ionic layer adsorption and reaction.